Report of executive for year ending 31st december, 1894 - National union of dock labourers in Great Britain & Ireland, Congrès (7 ; 1895 ; Liverpool)
Unanimously adopted by the Seventh annual congress held in the Free library, Willam Brown Street, Liverpool, from may 27th to may 31st, 1895, and ordered to be printed